Pengaruh Kualitas Pelayanan, Kinerja Pegawai dan Disiplin Kerja terhadap Kepuasan Masyarakat: (Studi Kasus pada Kantor Balaidesa Kubangsari) - Trisnawati Trisnawati; Hendri Sucipto; Gian Fitralisma (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims: 1) To determine and analyze the influence of public service quality on the satisfaction of the people of Kubangsari Village partially. 2) To find out and analyze the influence of employee performance on the satisfaction of the people of Kubangsari Village partially. Kubangsari Village community partially. 4) To determine and analyze the influence of Service Quality, Employee Performance and Work Discipline of Village Government Apparatus on Community Satisfaction in Kubangsari Village. The type of research used in this research is a quantitative approach, this research has a population of 6762 by taking as many samples as 99 respondents. Based on the analysis and discussion, a conclusion can be drawn where H1: Service Quality has a positive and significant effect on Community Satisfaction at the Kubangsari Village Hall Office with a t-value of 4.011 > 1.661 and a significant value of 0.000 < 0.05. H2: Employee Performance has a negative and insignificant effect on Community Satisfaction at the Balai Desa Kubangsari Office with a t-value of 0.495 > 1.661 and a significant value of 0.622 < 0.05. -count 4.914 > 1.661 and sig value. 0.000 < 0.05. H4: Service Quality, Employee Performance and Work Discipline simultaneously have a positive and significant effect on Community Satisfaction at the Kubangsari Village Hall Office with a value of F-count > F-table (45.010 > 2.697) and a significant value of 0.000 < 0.05.